2012
DOI: 10.1097/fjc.0b013e318271223c
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine Oxidase Contributes to Mitochondrial ROS Generation in an Experimental Model of Cocaine-Induced Diastolic Dysfunction

Abstract: Recent studies have shown that long-term cocaine use induces diastolic impairment and a myocardial oxidative stress. Recently, we have reported that cocaine-induced cardiac dysfunction may be due to a mitochondrial reactive oxygen species (ROS) overproduction, which occurs at the same time as xanthine oxidase (XO) activation. In this work, we hypothesized that XO activation contributes to mitochondrial ROS overproduction, which in turn contributes to diastolic dysfunction. To test this, we used a well-establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 29 publications
2
33
0
Order By: Relevance
“…These authors conclude that the reduced synthesis rate of mitochondrial proteins in response to ethanol exposure may be partly connected to depression in myocardial contractility and associated with functional damage of mitochondrial metabolism (120). In contrast, cocaine-induced cardiac dysfunction in rats revealed increased ROS production and decreased ATP synthesis in the IFM (137), which may occur through a xanthine oxidase-mediated mechanism (138). Hence, the majority of studies investigating the effects of drugs on mitochondrial subpopulations implicate SSM as being primarily affected.…”
Section: Pathological Influencementioning
confidence: 95%
“…These authors conclude that the reduced synthesis rate of mitochondrial proteins in response to ethanol exposure may be partly connected to depression in myocardial contractility and associated with functional damage of mitochondrial metabolism (120). In contrast, cocaine-induced cardiac dysfunction in rats revealed increased ROS production and decreased ATP synthesis in the IFM (137), which may occur through a xanthine oxidase-mediated mechanism (138). Hence, the majority of studies investigating the effects of drugs on mitochondrial subpopulations implicate SSM as being primarily affected.…”
Section: Pathological Influencementioning
confidence: 95%
“…[20]. Further amplification of this oxidative stress cycle occurs via ROS-induced ROS release by cardiomyocyte mitochondria [21,22] and inhibition of cardiac antioxidant systems [18]. In a rat model of cocaine-induced cardiac dysfunction, Vergeade et al [21] demonstrated complete prevention of cardiac dysfunction following cocaine administration in rats that were also treated with MitoQ, a mitochondrial-targeted antioxidant.…”
Section: Cardiomyocytesmentioning
confidence: 99%
“…One of the key mediators in ligandindependent transactivation of growth factor receptors, including PDGFR, are reactive oxygen species (ROS) (24). We and others have demonstrated induction of oxidative stress on exposure of vascular cell types to various HIV proteins, including Tat, and on exposure to illicit drugs, such as cocaine and opioids (11,25,26). Therefore, in this study, we explored the possibility of ROS-mediated ligand-independent activation of PDGFR in HPASMCs on combined treatment with cocaine and Tat.…”
Section: Human Immunodeficiency Virus (Hiv)-related Pulmonary Arteriamentioning
confidence: 99%